IMPLEMENTASI PEMBELAJARAN GEOMETRI BERBASIS RUMAH ADAT BATAK SEBAGAI UPAYA MENINGKATKAN NUMERASI SISWA SEKOLAH DASAR - Lubis, Jumaita Nopriani; Pelangi, Herman; Agustini, Rini; Rosmaimunah; Hasanah, Rini Yanti; Barokah, Khoiriah (CV. Alfa Pustaka, 2025)
This community service program aims to implement geometry learning based on the Batak traditional house (Rumah Bolon) to improve numeracy skills among elementary school students. The program was carried out through teacher training, classroom implementation, and evaluation stages at SD Muhammadiyah 2 Padangsidimpuan. A quantitative approach was applied using pre-test and post-test instruments to measure students’ numeracy improvement. The results showed 34% increase in students’ numeracy ability and a significant enhancement in teachers’ understanding of contextual, culture-based learning. The integration of Batak cultural values, especially Rumah Bolon geometry, was proven to make learning more meaningful and enjoyable.